INCLUSIVE EDUCATION - do Nascimento , Aniceia Pereira (Editora Impacto Científico, 2025)
This article addresses the importance of Inclusive Education in different contexts, including the COVID-19 pandemic. The role of technology in promoting educational inclusion is explored, highlighting how digital resources and online tools can support the personalization of teaching, the accessibility of teaching materials and communication between students and teachers. Furthermore, the challenges faced during the pandemic are discussed, such as the transition to remote teaching and the need to ensure equity in access to education. The article also emphasizes the importance of flexible and adaptable approaches, as well as adequate investments in infrastructure and emotional support for students. In short, the text highlights the ongoing need to promote Inclusive Education that meets the needs of all students, even in times of crisis. DOI: https://doi.org/10.56238/edimpacto2025.092-042